RISE: A minute with researcher: Prof. Dr Yarina Ahmad / Prof. Dr Yarina Ahmad - Ahmad, Yarina (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Prof. Yarina believed that sustainability should not only be focused on protecting the environment but the same energy should also be placed on keeping a balance between society and the economy. As the nation is becoming a developed country, it's crucial for every stratum of the society to embrace the concept of Keluarga Malaysia which reiterates the sense of belongings or simply termed inclusivity. No one should be left behind regardless of their academic, economic, social, and racial backgrounds. This is one of the many reasons that motivate her research group to do more to help society.